2016
DOI: 10.3961/jpmph.16.041
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Ethnic Discrimination and Depressive Symptoms Among Biethnic Adolescents in South Korea

Abstract: ObjectivesThis study investigated the association between perceived ethnic discrimination and depressive symptoms among biethnic adolescents in South Korea.MethodsWe performed a cross-sectional study of 4141 biethnic adolescents using data from the 2012 National Survey of Multicultural Families. Perceived ethnic discrimination was measured using the question “Have you ever been discriminated against or ignored because either of your parents is not a Korean?” with an assessment of depressive symptoms over the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…Adolescents whose parents originally came from a foreign country were at a greater risk of experiencing victimization compared to their peers. One possible explanation for these findings is that bi-ethnic adolescents in Korea are often exposed to ethnic discrimination, particularly from their peers [ 36 , 37 ]. Having a different appearance and coming from a different family background may cause them to appear conspicuous to their peer groups, particularly in a non-diverse environment such as Korea, therefore increasing their risk of becoming a target of violence.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents whose parents originally came from a foreign country were at a greater risk of experiencing victimization compared to their peers. One possible explanation for these findings is that bi-ethnic adolescents in Korea are often exposed to ethnic discrimination, particularly from their peers [ 36 , 37 ]. Having a different appearance and coming from a different family background may cause them to appear conspicuous to their peer groups, particularly in a non-diverse environment such as Korea, therefore increasing their risk of becoming a target of violence.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, positive friendship is connected with school satisfaction [ 16 ]. However, studies have shown that multicultural adolescents experienced difficulties in building friendships and school satisfaction, due to their experience of bullying in school, violence, and ethnic discrimination from their peer group [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent studies, bi-ethnic adolescents (adolescent children born of marriages of migrants or naturalized Koreans) can be vulnerable to violence at school as Koreans have strong intolerance towards other ethnicities, suggesting that experiencing violence at school and being left out will be closely related to depression [ 3 , 4 ]. Furthermore, Kim et al suggested that the low acculturation level of immigrant children and adolescents is connected to behavioral problems, such as adolescent delinquency [ 5 ].…”
Section: Introductionmentioning
confidence: 99%